PENGARUH TRANSFORMASI DIGITAL TERHADAP EFEKTIVITAS MANAJEMEN KINERJA KARYAWAN - Fadali Rahman; Mohammad Herman Djana; Dhini Febriani; Nurul Toyyibah; Subahri; Agim Mastiyar (Jurnal Riset Multidisiplin Edukasi, 2025)
Digital transformation in human resource management (HRM) plays a crucial role in enhancing employee productivity, which ultimately contributes to the effectiveness of employee performance management. This study aims to examine the impact of digital transformation on the effectiveness of employee performance management. The analysis results show that digital transformation has a significant impact on employee performance effectiveness by strengthening five key work principles: accuracy, speed, efficiency, safety, and problem-solving ability. With the right implementation strategy and adaptive human resource support, digitalization not only increases productivity but also creates a safer, more efficient, and sustainable work environment.